Migrants' perceptions of health system responsiveness and satisfaction with health workers in a South African Province - Janine A. White; Jonathan Levin; Laetitia C. Rispel (Taylor & Francis Group, 2020)
Background: There is global emphasis on quality universal health coverage (UHC) that is responsive to the needs of vulnerable communities, such as migrants. Objective: Examine the perceptions of migrants on health system responsiveness (HSR) and their satisfaction with health workers in public health facilities of a South African Province. Method: We conducted a cross-sectional study in 13 public health facilities. Following informed consent, we used a semi-structured questionnaire to collect sociodemographic information, patient perceptions of HSR and their satisfaction with health workers. Two open-ended questions gave patients the opportunity to comment on the health facility visit. We applied descriptive and multivariate analyses to our data, and thematic analysis to the qualitative responses. Results: A total of 251 migrant patients participated in the study, giving a response rate of 80.7%. The majority of patients were female (81.1%), and the mean age was 31.4 years. 30.0% of patients reported that they waited too long; 94.3% that the consulting nurse or doctor listened to them; and 89.4% that they received information about their condition. However, 81.7% said they did not know the name of the consulting nurse or doctor. The mean scores on patients' satisfaction with health workers ranged from 7.0 (95% CI 6.42-7.63) for clerks, 7.7 (95% CI 7.4-8.0) for security guards, 7.4 (95% CI 7.1-7.6) for nurses and 8.3 (95% CI 7.93-8.63) for doctors. The predictors of patient satisfaction with nurses were being given information about their condition; polite treatment, time spent in facility, whether they received prescribed medicines; and stating that they would refer the health facility to family/friends. Four overlapping themes emerged: health workers' attitudes; time waited at the health facility, communication difficulties; and sub-optimal procedures in the health facility. Conclusion: UHC policies should incorporate migrant patients' perceptions of HSR and the determinants of their satisfaction with health workers.